2017
DOI: 10.1016/j.ijlp.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

How family members of mentally ill offenders experience the internment measure and (forensic) psychiatric treatment in Belgium: A qualitative study

Abstract: Mentally ill offenders in Belgium can be subjected to mandated care under an "internment measure" if they are viewed as a danger to society. This study investigated how family members of mentally ill offenders experience this internment measure and view the (forensic) psychiatric treatment of their relative. Semi-structured interviews were conducted with 24 relatives and analysed using Nvivo 11. Six different themes emerged: (1) the criminal offence and the internment measure as an additional stigma, (2) ambiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 30 publications
2
51
0
1
Order By: Relevance
“…This may partly reflect the needs of the participating population of family members in our study. Indeed, family members of mentally ill offenders often feel strongly isolated, chronically burdened, and stigmatised by the mental illness and criminal offence, and that they lacked professional and social support both in our groups as well as in international research studies (Nordström et al., ; Rowaert, Vandevelde, Lemmens, & Audenaert, ; Tsang et al., ). Yet, other therapeutic factors – such as ‘interactional confirmation,’ ‘expressing mutual positive feelings,’ ‘experiencing positive feelings,’ ‘forgetting own problems through helping others,’ ‘hope from seeing progress in others,’ ‘guidance from therapists,’ and ‘getting interpersonal feedback’ – gradually become more frequently reported over the course of the intervention.…”
Section: Discussionmentioning
confidence: 94%
“…This may partly reflect the needs of the participating population of family members in our study. Indeed, family members of mentally ill offenders often feel strongly isolated, chronically burdened, and stigmatised by the mental illness and criminal offence, and that they lacked professional and social support both in our groups as well as in international research studies (Nordström et al., ; Rowaert, Vandevelde, Lemmens, & Audenaert, ; Tsang et al., ). Yet, other therapeutic factors – such as ‘interactional confirmation,’ ‘expressing mutual positive feelings,’ ‘experiencing positive feelings,’ ‘forgetting own problems through helping others,’ ‘hope from seeing progress in others,’ ‘guidance from therapists,’ and ‘getting interpersonal feedback’ – gradually become more frequently reported over the course of the intervention.…”
Section: Discussionmentioning
confidence: 94%
“…in terms of its format and content) which was designed to foster a context that enabled family members to disclose their emotions. This feature is important as many family members of PMIO are confronted with a diverse range of emotions, a double stigma, and poorer well-being, which warrants particular attention during treatment (Moses, 2010;Ridley et al, 2014;Rowaert et al, 2017;Tsang et al, 2002). Moreover, many participants were listened to by others (i.e., therapists and family members) for the first time, which may also have positively influenced their emotional well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that family members struggle with feelings of anxiety, powerlessness, and grief (Nordström, , Kullgren, & Dahlgren, 2006;Rowaert et al, 2016). As society tends to doubly stigmatise PMIO through the application of constructs including that of 'psychiatric patient' and 'criminal', they frequently experience guilt and shame, and feel socially isolated (Absalom-Hornby, Gooding, & Tarrier, 2011;Pearson & Tsang, 2004;Rowaert et al, 2016;Rowaert, Vandevelde, Lemmens, & Audenaert, 2017;Tsang et al, 2002). Family members reportedly struggle with feelings of (self-)blame which often exacerbates their perceived burdens and diminishes their sense of hopefulness (Moses, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This further increases their levels of stress (Rowaert et al., ). Despite these burdens, and the lack of support from family, friends, and professionals, many family members continue to support their relative, which only increases their needs (Loukissa, ; Marsh & Johnson, ; Rowaert, Vandevelde, Lemmens, & Audenaert, ; Wynaden, ).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, few interventions have been developed to support family members of OMIs (Absalom, McGovern, Gooding, & Tarrier, ; Absalom‐Hornby, Gooding, & Tarrier, ; Geelan & Nickford, ). This might be due to the fact that family interventions in forensic settings may face particular challenges, including: the separate living arrangements of the OMI and their relatives; the distances between forensic services and the family members’ residence; the traumas family members experience (e.g., violence within the family, court proceedings, visits to prison) that are linked to the criminal activities and the relative's mental health problems (Fadden, ; Rowaert et al., , ). Forensic professionals often lack training in family‐based support, and appropriate facilities and/or time are often not available (Fadden, ).…”
Section: Introductionmentioning
confidence: 99%